Analisis Frekuensi Natural Velg Ring 16 Menggunakan Finite Element Method - Bagus Prasetiyo, Angger; Kartinasari Ayuhikmatin Sekarjati; Sutrisna; Iman Pradana A. Assagaf (ReTII, 2022)
Wheels are one of the automotive vehicle parts that continue to see design advancement and different shapes. There are two different kinds of alloy wheels in use by the general public: steel alloy wheels and aluminum alloy wheels. The spokes of these aluminum alloy wheels typically rupture due to force and center that exceed the maximum stress value, or the rim of the rim is damaged due to plastic deformation. Using the ANSYS Workbench software, the natural frequency shape of the ring 16 rim was compared to its normal shape to identify how the rim would flex in the event of a failure and to make it simpler for designers to examine the design. The ring 16 wheel modeling material used in this study is aluminum alloy. ANSYS Workbench is used to analyze vibration modes. The natural frequencies of the 16 ring wheels as determined by analysis are 207.68Hz, 209.1Hz, 347.37Hz, 348.37Hz, 416.45Hz, 443.42Hz, 860.36Hz, 863.1Hz, 1166.7Hz, and 1168.8Hz. With a rise of 416.94Hz, the sixth vibration mode to the seventh order has the biggest frequency increase. The 16 ring wheels’ maximum deformation measurements are 16, 592, 16,593, 21,887, 21,965, 11, 388, 11, 48, 22.231, 22.445, 13,731 and 13, 537 millimeters.